Studi Etnobotani Bambu Oleh Masyarakat Dayak Kanayatn Di Desa Saham Kecamatan Sengah Temila Kabupaten Landak - Mukarlina, Munziri, Riza Linda, (Jurnal Protobiont, 2013)
People who live in the village of Saham, at Landak Regency are entirely Kanayatn Dayak ethnic. This enhnic community utilizes bamboo in daily life. The aim of this research was to investigate the use of bamboo by Kanayatn Dayak community who live in the village of Saham, at Sengah Temila subdistrict, at Landak regency. This research is conducted for three months, from April to June 2011. The method used is interview and observation. Based on the finding on the research in the village of Saham, at Sengah Temila Subdistrict, at Landak Regency, there are nine species of bamboo which are from four genera: Bambusa balcoa, Bambusa eutuldoide, Bambusa glaucophylla, Bambusa multiplex, Gigantochloa atter, Schizostachyum brachycladum, Schizostachyum lima, Schizostachyum sp dan Thyrsostachys siamensis. Kanayatn Dayak community in the village of Saham, at Sengah Temila subdistrict, makes use of bamboo for food, construction, crafts, musical instruments, ethnic ceremonies, and ornamental plants.